Editing Software as Strategy Value - M D Aulia; A Pratama; W Wildan; F Elzami; Maulidina Aisyah (Peneliti.net, 2021)
This study aims to see the function of using the software as a non-verbal strategy to value the artwork's value in design and videography. In editing software, several tools will be used to support the creation of non-verbal artistic values. This study used a descriptive method to collect data and describe how problems in using editing software often occur because a portion of an editing application can be used perfectly to make a form of art value less maximal. In an editing software, the research results show that the use of editing software such as Adobe Illustrator, Photoshop, and Adobe Premiere is a support for the creation of a form of art so that it is easy to express creative ideas and apply them in the form of non-verbal artistic values. Notifying the function and use of editing software in a work of art will facilitate and utilize non-verbal strategy editing software application in the value of art such as design and videography.